Crizotinib-induced pancreatic pseudocyst: a novel adverse event. (8th September 2015) - Ishida, Hiroo; Ichikawa, Wataru; Sasaki, Yasutsuna
Abstract : Crizotinib is a tyrosine kinase inhibitor that demonstrates a dramatic tumour response in patients with advanced non-small cell lung cancers harbouring anaplastic lymphoma kinase (ALK) rearrangement. The pancreatic cyst has never been reported in patients who received crizotinib, whereas crizotinib-induced renal cysts developed in 4% of patients who were enrolled in clinical trials. We present the case of a 54-year-old man who was diagnosed with non-small cell lung cancer harbouring ALK rearrangement. After the start of treatment with crizotinib, we accidentally encountered the pancreatic pseudocyst without abdominal symptom and elevated serum pancreatic enzymes. In this report, we describe a case of pancreatic pseudocyst that appeared after starting treatment with crizotinib and regressed after treatment withdrawal.